PENERAPAN PAKET EDUKASI CHATTING DAN GAME PINTAR TERHADAP STRES DAN PEMAHAMAN PACARAN SEHAT PADA REMAJA DI MASA PANDEMI COVID-19 - Sanjiwani, Ida Arimurti; Pramitaresthi, I Gusti Ayu (Coping: Community of Publishing in Nursing; Vol 11 No 3 (2023): Juni 2023, 2023)
The Covid-19 pandemic is a global disaster that has had an impact on every aspect of human life, as well as in adolescents. The existence of physical distance and restrictions on direct association in adolescents who tend to be active can have an impact on psychological stress. They who are start to know about love and dating have to changes in habits. The aim of this study was to identify chatting and smart games health education packages toward adolescent stress levels and healthy dating knowledge in adolescent during Covid-19 pandemic. This study used a pre-experimental research design with one group pe-test and post-test design. 60 samples were chosen by simple random sampling. Data was collected by using General Anxiety Disorder 7 (GAD7) and knowledge of healthy dating questionnaire. The results of bivariate analysis with Wilcoxon test showed that there was an effect of chatting interventions and games on adolescent stress levels and also in dating knowledge (p < 0,001).